Growth Mindset sebagai Determinan Perilaku Kerja Inovatif: Peran Pemberdayaan Psikologis sebagai Mediator - Nisrina Hanun Iftadi; Afriza Animawan Arifin; Putri Febryasti Ronita (Jurnal Ilmu Perilaku, 2024)
The era of globalization affects the business challenges faced by organizations, including higher-education institutions. Hence, it is such an essential thing for higher-education institutions to enhance their workforce's innovation in order to respond to the needs of society through the implementation of Tri Dharma Perguruan Tinggi. This research was aimed to empirically test the role of psychological empowerment as a mediator of the association between growth mindset and innovatife work behavior of lecturer. This study was conducted using a correlational quantitative approach with method of survey. The participants of this study consist of 113 permanent lecturers at University X in Surakarta who were selected using convenience sampling techniques. Research variables were measured using the innovative work behavior scale, empowering leadership questionnaire, and growth mindset scale. Research hypothesis analysis was carried out using path analysis. The analysis results revealed that psychological empowerment fully mediated the association between between growth mindset and innovative work behavior of lecturer. These findings show the importance of the role of growth mindset in cultivate the feeling of being empowered psychologically and how it impacts the level of innovative work behavior among lecturer.